KESADARAN IBU RUMAH TANGGA DALAM MENGELOLA SAMPAH RUMAH TANGGA MELALUI PENERAPAN REDUCE, REUSE DAN RECYCLE DI KECAMATAN AIR SUGIHAN - Nasution, Warnida; Husin, Azizah; Nengsih, Yanti Karmila (Jurnal Pendidikan Sepanjang Hayat, 2023)
This research was motivated by the problem of household waste that is not managed properly, which results in environmental damage. The purpose of the study was to determine the awareness of housewives in managing waste through the application of reduce, reuse and recycle in Air Sugihan District. This study used a Quasi-Experimental quantitative approach. By using Pretest and Posttest Control Group Design type research design. The sampling technique used was a random sampling technique with a total of 87 respondents divided into a control group and an experimental group. Data collection was carried out by questionnaire (pretest and posttest) and observation. The results in this study showed an increase after being given treatment, namely socialization. Awareness in the control group obtained a percentage result of 55%, this result falls into the low category. Awareness in the experimental group before being given treatment (pretest) was obtained in the low category with a percentage of 58%. After being given treatment, namely socialization, posttest results showed an increase, namely an average percentage of 78% included in the high category. The observations also show that this study has changes in behavior in housewives in managing waste, but these changes are not comprehensive. Based on these results, the level of awareness of housewives is included in the stage of Conscious Competence, which is the stage of a person who is confident and does it right, but there needs to be practice and hard work to produce a habit.